Christian History as World History: A Review Essay - Carpenter, Joel A. (International bulletin of mission research, 2020)
This review essay discusses the status of "World Christianity" as a field of study, then highlights the features of the book at hand. It is an exercise in world history more than church history, focusing on how Christianity in various parts of the world responded to the twentieth century's greatest challenges. The book addresses the rise of millenarianism and fundamentalism, neo-orthodoxy, liberation theology, Pentecostalism, and ecumenism. But its more intent focus is on how Christianity addressed the century's world wars, colonialism, nationalism, secularism, rise of radical Islam, human rights, migration, and the growing power of the state.